Enhancing Nuclear Security Culture in Organizations Associated with Nuclear and Other Radioactive Material Technical Guidence. - IAEA (IAEA Nuclear Security Ser., 2021)
Nuclear security culture is an important component of an effective nuclear security regime, as it serves as a tool to improve the performance of the human component at nuclear facilities and organizations to counter both insider and outsider threats. Security culture connotes not only the technical proficiency of the people but also their awareness of security risks and motivation to follow established procedures, comply with regulations and take the initiative when unforeseen circumstances arise. A workforce made up of individuals who are vigilant, who question irregularities, execute their work diligently and exhibit high standards of personal and collective behaviour is able to achieve effective nuclear security. Building upon this understanding of the importance of a strong nuclear security culture, this publication provides practical guidance on how to implement a systematic nuclear security culture enhancement programme."--Publisher's description